SF3B4 is decreased in pancreatic cancer and inhibits the growth and migration of cancer cells - Wentao Zhou; Ning Ma; Hao Jiang; Yefei Rong; Yuezhen Deng; Yuanyuan Feng; Hongxu Zhu; Tiantao Kuang; Wenhui Lou; Dong Xie; Dansong Wang (Tumor Biology)
Splicing factor 3b subunit 4, a critical component of pre-message RNA splicing complex, has been reported to play an important part in the tumorigenesis. However, the expression pattern and biological role of splicing factor 3b subunit 4 in pancreatic cancer have never been investigated. In this study, we found that both the messenger RNA ( p < 0.001) and protein level of splicing factor 3b subunit 4 were decreased significantly in pancreatic cancer specimens compared with their adjacent normal tissues. Overexpression of splicing factor 3b subunit 4 in pancreatic cancer cells inhibited cell growth and motility in vitro, while suppressing splicing factor 3b subunit 4 expression promoted the proliferation and migration of pancreatic cancer cells. In addition, splicing factor 3b subunit 4 was found to inhibit the activity of signal transducer and activator of transcription 3 signaling via downregulating the phosphorylation of signal transducer and activator of transcription 3 on a tyrosine residue at position 705. Taken together, these findings demonstrated that splicing factor 3b subunit 4 acted as a suppressive role in pancreatic cancer and indicated that restoring the function of splicing factor 3b subunit 4 might be a strategy for cancer therapy.